Thinking differently about local economic development and governance in secondary cities in South Africa - A conceptual analysis of the possibilities of problem driven iterative adaption (PDIA) - Du Plooy, Louis Johannes (Graduate School of Development Policy and Practice, 2017)
Local economic development successes and failures at municipal level, and specifically in secondary cities in South Africa, is deeply influenced by the constitutional imperatives for establishing developmental local government. The local planning, economic development and policy frameworks introduced between 1999 and 2006 were largely based on, and moulded according to, the wave of new public management paradigms and public sector reform 'good governance best practises' implemented in South Africa post the 1994 democratic elections. The study makes two claims about municipal designs and practises, one that the governance design for these expressions of developmental local government in South Africa has been driven by solution based and theoretical mechanisms rooted in primarily new public management frameworks and development approaches. The second claim is that this development approach manifested in practise in specific plans and frameworks which municipal governments and entities are required to implement and this implementation is characterised by mimicry and isomorphism through compliance, specifically in intermediate cites The motivation for the study, and the third claim which the study investigates, is that the implementation of these plans in practise is not doing so well in terms of delivering the results as envisaged, and secondary cities and towns are often in economic, social and service delivery crises and exhibit very high levels of spatial exclusion despite the local economic development profiles and governance arrangements in these settings increasingly being a matter of policy discussion and debate. The study then introduces a proposed alternative by focusing on implementation at local level and explores how things might be done differently. It looks at the possible contribution of the current search for more effective public service reform, generally referred to as 'doing development differently' or 'smart(er) development', to this local economic development debate. Through a conceptual analysis and application of the approaches and methodologies introduced by problem driven iterative adaption, the study identifies possible different approaches for local economic development in secondary cities and explains what it looks like. The study concludes that doing local economic differently in intermediate settings in South Africa can provide more realistic expectations for the results of local economic development initiatives through fundamentally rephrasing the problem as one that matters, and make recommendations for approaches through which problem driven iterative adaptation processes and practises can be introduced in the context of the institutional constraints present in these intermediate settings.